Solid Waste Management in Indonesia: a Review - Desrianti; Ikma Inur Hidaiyah; Halma; Nurosa Sabila (Journal of Epidemiology and Health Science, 2026)
Background: Solid waste consists of discarded materials generated from human activities and natural processes in solid form. Rapid population growth and urbanization in Indonesia have significantly increased waste generation, creating challenges in collection, treatment, and disposal systems. Despite national policies promoting waste reduction and sustainable management, waste handling remains largely dependent on landfill disposal. Composting has emerged as an effective approach for managing organic waste by reducing landfill burdens while producing valuable soil amendments. Objectives: This study aimed to assess solid waste management through composting technology and evaluate its implications for public health and environmental sustainability. Method: A systematic review was conducted using secondary data obtained from scientific articles, research reports, and publications related to solid waste management, composting technology, and public health. Results: The review showed that composting and community-based waste management initiatives improve waste handling efficiency, reduce pressure on landfills, enhance public participation, and support environmental conservation. Compost production from organic waste improves soil fertility and reduces environmental pollution. However, challenges remain, including inadequate infrastructure, limited community engagement, and the growing proportion of non-biodegradable waste. Conclusion: Composting technology provides environmental, economic, and public health benefits by reducing waste volume, mitigating pollution, lowering greenhouse gas emissions, and promoting healthier living environments. Keywords: solid waste management, composting technology, public health, organic waste.